2010
DOI: 10.3174/ajnr.a2050
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Long-Term Outcome after Endovascular Stroke Treatment: The Totaled Health Risks in Vascular Events Score

Abstract: BACKGROUND AND PURPOSE: Endovascular treatments are being increasingly used in acute ischemic stroke, and better tools are needed to determine which patients may benefit most from these techniques. We hypothesized that specific chronic diseases can be used, along with age and stroke severity, to predict endovascular stroke treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
151
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 11 publications
3
151
1
Order By: Relevance
“…[5][6][7] The receiver operating characteristic areas under the curves for THRIVE score to predict good outcome and death in our study, which involved only patients who did not receive tPA therapy, were similar to areas under the curves reported for THRIVE to predict outcomes in other acute stroke treatment contexts. [5][6][7] Based on our results and on those of previous studies, the THRIVE score seems to work well in patients from Europe, North America, and East Asia.…”
Section: Discussionsupporting
confidence: 55%
“…[5][6][7] The receiver operating characteristic areas under the curves for THRIVE score to predict good outcome and death in our study, which involved only patients who did not receive tPA therapy, were similar to areas under the curves reported for THRIVE to predict outcomes in other acute stroke treatment contexts. [5][6][7] Based on our results and on those of previous studies, the THRIVE score seems to work well in patients from Europe, North America, and East Asia.…”
Section: Discussionsupporting
confidence: 55%
“…26 The THRIVE score author group trichotomized NIHSS scores (≤ 10, 11-20, and ≥ 21) and concluded that the breakdown of the scale could effectively predict those very likely, moderately likely, and least likely to experience good outcome subsequent to endovascular stroke treatment, respectively. 20 Yet another analysis reports that patients who experienced futile recanalization, defined as successful removal of the thrombus without corresponding clinical improvement, had higher median baseline NIHSS scores (19) compared with those with nonfutile recanalization pursuant to IAT (14). 29 Multiple groups report that an NIHSS score of < 10 is a predictor of a good clinical outcome for patients treated with IAT.…”
Section: Individual Predictors Of Futile Recanalizationmentioning
confidence: 99%
“…20 A history of stroke, coronary artery disease, or congestive heart failure has also been associated with worse outcomes in patients given endovascular therapy for acute cerebral ischemia. 20,26,39 Other authors have investigated the impact of admission cholesterol level on outcome after ischemic stroke thrombolysis in 104 patients who received IVtPA, intraarterial tPA, or mechanical thrombus retrieval. Lower levels of low-density lipoprotein cholesterol, with or without statin treatment, were independently and significantly correlated with a higher risk of symptomatic hemorrhagic transformation after revascularization therapy.…”
mentioning
confidence: 99%
“…Pretreatment Totaled Health Risks in Vascular Events (THRIVE) scores were calculated on the basis of published criteria. 6 The THRIVE score has been validated as a simple pretreatment scoring tool to predict clinical outcome, mortality, and symptomatic hemorrhage after ERT and is calculated on the basis of age, NIHSS score, and history of atrial fibrillation, diabetes, and hypertension.…”
Section: Data Sourcesmentioning
confidence: 99%
“…1,2 However, subsequent single-arm studies of mechanical embolectomy have observed less impressive results 3,4 and suggest that outcomes are related to several key factors, including patient characteristics (age, co-morbidities, and stroke severity) and treatment factors (time to reperfusion). [5][6][7][8][9][10] Radiographic features, including pretreatment tissue status by NCCT of the head, brain MR imaging, and perfusion imaging (CTP or MR perfusion [MRP]), may improve patient selection. 5,8,9,11 Few studies have compared NCCT-based selection with perfusion imaging-based selection of patients for ERT following acute ischemic stroke.…”
mentioning
confidence: 99%